2021
DOI: 10.1021/acsami.1c12742
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Photoinduced Recovery Mystery in Conjugated Polymer-Based Transistor Memory

Abstract: A straightforward mechanism for the photorecovery behavior of photoresponsive nonvolatile organic field-effect transistor (OFET) memories is proposed by employing a commercially available conjugated polymer, the poly(9,9-dioctylfluorene) (PFO), the conjugated monomer fluorene (FO), and the nonconjugated poly(vinyl alcohol) (PVA), as charge storage layers beneath the semiconducting pentacene layer. As photoexcitons are generated upon light exposure, the respective charges recombine with the trapped charges in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…[1,18,19] For an ONVM, its typical configuration is a conventional transistor with an additional charge-trapping layer between the semiconductor channel and gate contact. [20] The charge-trapping layer, such as floating-gate dielectrics, [17,[21][22][23][24][25] ferroelectric materials, [26][27][28][29][30][31][32] and polymer electrets, [33][34][35][36][37][38][39][40] can have a significant impact on the charge transportation in the active channel as well as the memory performance of the ONVM. The floating-gate ONVMs utilize nanoparticles of metal or semiconductor embedded in the dielectric layer as the chargetrapping sites to achieve high-density storage.…”
Section: High-performance Pentacene-based Field-effect Transistor Mem...mentioning
confidence: 99%
“…[1,18,19] For an ONVM, its typical configuration is a conventional transistor with an additional charge-trapping layer between the semiconductor channel and gate contact. [20] The charge-trapping layer, such as floating-gate dielectrics, [17,[21][22][23][24][25] ferroelectric materials, [26][27][28][29][30][31][32] and polymer electrets, [33][34][35][36][37][38][39][40] can have a significant impact on the charge transportation in the active channel as well as the memory performance of the ONVM. The floating-gate ONVMs utilize nanoparticles of metal or semiconductor embedded in the dielectric layer as the chargetrapping sites to achieve high-density storage.…”
Section: High-performance Pentacene-based Field-effect Transistor Mem...mentioning
confidence: 99%
“…The same approach was adopted by Chen et al, revealing an improved memory ratio of 10 7 over 4,000 s under electrical writing and photoassisted electrical erasing processes with 405 nm light. [ 106 ] However, the semiconducting nature of PFO deteriorates the stability of trapped charges, and destructive readout with gate bias is necessary to apply to operate these devices.…”
Section: Development Of Phototransistor Memorymentioning
confidence: 99%
“…The recent studies reported that using photoactive triphenylamine-based donor-acceptor polymers as the charge storage layer could significantly decrease the photorecovery time, which caused by the excellent intramolecular dipole moment to facilitate the excitons' dissociation, and then demonstrate that the generated excitons in charged photoactive layer dominate the phenomenon. [10,16] On the other hand, an ultrafast photoprogramming memory, using the recombination of the formed interlayer excitons at the interface between a semiconductor and a novel aggregation-induced emission (AIE)-photoactive charge storage electret has demonstrated. [6] The electret comprising of photoactive perovskite nanoparticles blended in polystyrene (PS) has exhibited well photoresponsibility of nonvolatile memory.…”
Section: Tunneling-effect-boosted Interfacial Charge Trapping Toward ...mentioning
confidence: 99%
“…On top of that, the exhibition of memory behaviors is mediocre compared to that of the typical OFET memory with single charge storage layer structure. [16] In this paper, we introduced the design concept of tunnelingeffect-assisted interfacial charge trapping for budget effective, facile and versatile device manufacturing for more practical use, and multifunctional transistor for photomemory. An ultrasimple device comprising p-type pentacene active channel and octadecyltrimethoxysilane (OTS)-modified layer portrayed in Figure 1a was constructed as a proof-of-concept model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation